Myeloid microvesicles in cerebrospinal fluid are associated with myelin damage and neuronal loss in mild cognitive impairment and Alzheimer disease. Issue 6 (16th October 2014) - Agosta, Federica; Dalla Libera, Dacia; Spinelli, Edoardo Gioele; Finardi, Annamaria; Canu, Elisa; Bergami, Alessandra; Bocchio Chiavetto, Luisella; Baronio, Manuela; Comi, Giancarlo; Martino, Gianvito; Matteoli, Michela; Magnani, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> Objectives We have described cerebrospinal fluid (CSF) myeloid microvesicles (MVs) as a marker of microglia activation during neuroinflammation in Alzheimer disease (AD), and characterized their ability to produce toxic amyloid β1–42 (Aβ1–42) oligomers from aggregated or soluble substrate. The aim of this study is to investigate the association of CSF myeloid MVs with neuroimaging, clinical, and paraclinical data in AD and mild cognitive impairment (MCI). Methods We collected CSF from 106 AD patients, 51 MCI patients, and 29 neurologically healthy controls. We examined CSF myeloid MV content and AD markers. A subgroup of 34 AD and 21 MCI patients underwent structural and diffusion tensor MRI. Results Higher levels of myeloid MVs were found in the CSF of AD patients and MCI patients converting within 3 years relative to controls, but also, at a lower level, in MCI patients not converting to AD. CSF myeloid MVs were associated with Tau but not with Aβ1–42 CSF levels. CSF MVs levels correlated with white matter (WM) tract damage in MCI, and with hippocampal atrophy in AD. Interpretation Microglial MVs are neurotoxic and myelinotoxic in the presence of Aβ1–42. CSF myeloid MVs, mirroring microglia activation and MV release, are associated with WM damage in MCI and hippocampal atrophy in AD. This suggests that hippocampal microglia activation, in the presence of Aβ1–42 in excess, produces neurotoxic and oligodendrotoxic oligomers that, through WM tract damage, spread disease to neighboring and connected areas, causing local microglia activation and propagation of disease through the same sequence of events. Ann Neurol 2014;76:813–825